Analysis of Forest Fire Behaviour by Advanced Computer Fire Simulators - Jan Glasa; Peter Weisenpacher; Ladislav Halada (Communications - Scientific letters of the University of Zilina, 2011)
Computer modelling of dangerous phenomena related to fire in forest or in wildland-urban interface is an important tool to support emergency planning for such complicated events. In this paper, the use of FARSITE (Fire ARea SImulaTor), adapted for real conditions in Slovak Paradise National Park (Slovakia), and WFDS (Wildland-urban interface Fire Dynamics Simulator) for simulation of forest fires and fires in wildland-urban interface is demonstrated. Computer reconstruction of an especially tragic destructive forest fire happened in 2000 as well as simple examples of automobile fire in wildland-urban interface are illustrated.